2021
DOI: 10.1371/journal.pone.0256536
|View full text |Cite
|
Sign up to set email alerts
|

The impact of chronic comorbidities at the time of breast cancer diagnosis on quality of life, and emotional health following treatment in Canada

Abstract: Introduction Advances in breast cancer screening and treatment have led to an increasing number of breast cancer survivors. The objective of this study was to determine the impact of comorbidities on self-reported quality of life (QOL) and emotional health following a breast cancer diagnosis and treatment. Methods Women with a personal history of breast cancer (N = 3,372) were identified from the cross-sectional Canadian Partnership Against Cancer (CPAC) Experiences of Cancer Patients in Transitions Survey. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 38 publications
0
11
1
Order By: Relevance
“…A moderate level of total QoL was reported in some countries such as Iran and India as observed in the current study (Kiadaliri, Bastani & Ibrahimipour, 2012;Muthanna, Khairkar & Hurtig, 2017). BC patients in some countries like Canada, Saudi Arabia, Pakistan, Korea, and Malaysia had reported higher total QoL (Arneja & Brooks, 2021;Imran et al, 2019;Muthanna et al, 2021;Yusoff et al, 2022) whereas a lower level of total QoL was found among certain BC patients in China and Colombia (Ban et al, 2021;Cui, Wang & Wang, 2021;Finck et al, 2018). In our study, the observed low level of social QoL has greatly contributed to lowering the total QoL to a moderate level.…”
Section: Discussioncontrasting
confidence: 46%
“…A moderate level of total QoL was reported in some countries such as Iran and India as observed in the current study (Kiadaliri, Bastani & Ibrahimipour, 2012;Muthanna, Khairkar & Hurtig, 2017). BC patients in some countries like Canada, Saudi Arabia, Pakistan, Korea, and Malaysia had reported higher total QoL (Arneja & Brooks, 2021;Imran et al, 2019;Muthanna et al, 2021;Yusoff et al, 2022) whereas a lower level of total QoL was found among certain BC patients in China and Colombia (Ban et al, 2021;Cui, Wang & Wang, 2021;Finck et al, 2018). In our study, the observed low level of social QoL has greatly contributed to lowering the total QoL to a moderate level.…”
Section: Discussioncontrasting
confidence: 46%
“…Along with an increased vulnerability to breast cancer, increasing age also carries a higher risk of other health problems [10,11]. Postmenopausal breast cancer patients frequently have one or more pre-existing comorbid conditions at the time of diagnosis (eg, arthritis or other rheumatologic diseases, cardiovascular disease, hypertension, chronic obstructive pulmonary disease (COPD), osteoporosis, and diabetes mellitus) [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Recent efforts were made toward survivors’ quality of life, including integrating information on multi-morbidities into survivorship care. The reason is that worse physical and mental health have a negative impact on survival outcomes of breast cancer patients [ 16 , 17 ]. Therefore, identifying racial/ethnic differences and understanding survivors’ physical and mental health may assist providers in recommending the appropriate follow-up care with timely CRC screening.…”
Section: Introductionmentioning
confidence: 99%